Reconstruction Of The Expansion Of Criminal Sanctions For Money Laundering Crimes Through Non-Conviction Based (Ncb) Asset Forfeiture And In Rem Lawsuit - Dhumilah, Dewic Sri Ratnaning; Mustofa, Muhammad; Shodiq, Md. (Asian Journal of Social and Humanities, 2025)
The construction of criminal sanctions for money laundering (TPPU) in Indonesia is still a classic problem that has not been successful. The dependence on proof of the original crime in the criminal process is often the main obstacle in its enforcement. This is compounded by the weakness of legal norms related to the process of confiscating assets resulting from money laundering. Data from the 2021 PPATK National Risk Assessment (NRA) report, the estimated value of the proceeds of crime reached IDR 44,200,000,000,000 (forty-four trillion two hundred billion rupiah) and has not been confiscated by the state. The results of the PPATK analysis also stated that the length of the TPPU criminal justice process was a factor. The procedure for criminalizing money laundering only focuses on fulfilling the elements of the crime while the object of the crime has always not received attention and has not been a special consideration as the main door to arresting the perpetrators of the crime even though there are indications of improper acquisition of assets. In Australia and America, the TPPU criminal process uses a combined criminal and civil system, namely through the in rem lawsuit method in the NCB concept which can be the main door in enforcing TPPU. The use of the in rem method in enforcing TPPU does not only focus on the purpose of "asset confiscation" but also finding the perpetrators of the crime. So in this study the author reconstructs the expansion of the criminal punishment for money laundering (TPPU) which will be determined through NCB Asset Forfeiture and In Personam. Using the normative juridical method to analyze the concept of the approach to expanding the punishment of money laundering through NCB Asset Forfeiture and in personam in doctrine, theory, rules and concepts, as well as a comparative study of its application within the framework of the Theory of Justice, Theory of Asset Confiscation and Alternative Punishment Theory. So it can be concluded that the reconstruction of the expansion of TPPU criminalization through NCB asset forfeiture and In personam is an alternative TPPU criminalization that can be implemented considering that the current positive legal provisions cannot accommodate the actions of criminals who continue to enjoy the proceeds of crime, which greatly injures the sense of justice for victims and/or the state, even though we have ratified the UNCAC since 2003. For the sake of achieving justice (gerechtgkeit) and the realization of laws that provide certainty (rechtssicherheit) and benefits (zweckmassigkeit).